Factors shaping large‐scale gradients in seed physical defence: Seeds are not better defended towards the tropics - Si‐Chong Chen; Angela T. Moles (Global Ecology and Biogeography, 2018)
Aim Previous studies have shown that seed predation is not more intense towards the tropics. One possible explanation for this finding is that seeds might be better defended at lower latitudes. Our goal was to provide the first broad‐scale, quantitative analysis of the latitudinal gradient in physical investment in tissues surrounding seed reserve. In order to understand which factors underpin large‐scale gradients in seed defence, we also quantified relationships between seed physical defence and climate, seed predation, seed mass, fruit type and growth form. Location Twenty‐five sites ranging from 15°30′ to 43°35′ S along the east coast of Australia. Time period 2015. Major taxa studied Seed plants. Methods We measured the biomass ratio of protective tissue to seed reserve (hereafter, seed physical defence) for 250 species–site combinations, with separate consideration of the structures protecting the seed during exposure to pre‐dispersal seed predation and post‐dispersal seed predation. Results Contrary to expectations, cross‐species analyses showed that pre‐dispersal seed physical defence was greater towards high latitudes, whereas there was no latitudinal gradient in post‐dispersal seed physical defence. Phylogenetic analyses revealed no significant relationship between latitude and either pre‐dispersal or post‐dispersal seed physical defence. There was no relationship between either pre‐dispersal or post‐dispersal seed physical defence and seed predation or seed mass. Fleshy‐fruited or herbaceous species invested less in pre‐dispersal seed physical defence while suffering less pre‐dispersal seed predation than did dry‐fruited or woody species. Main conclusions Our findings indicate that natural seeds in their natural habitats are not better defended at lower latitudes. Together with recent studies of latitudinal gradients in seed predation, leaf herbivory and defence, this study adds to the growing body of evidence that challenges the idea of a declining latitudinal gradient in biotic interactions and therefore casts doubt on the traditional understanding of the factors driving the latitudinal gradient in plant diversity.